3D Facial Effects of a Simulated Dental Build‐up. Issue 6 (29th June 2016) - Sterenborg, Bernadette A. M. M.; Maal, Thomas J.J.; Vreeken, Rinaldo D.; Loomans, Bas A.C.; Huysmans, Marie‐Charlotte D. N. J. M.
ABSTRACT: Objective: The purpose of this study was to evaluate the 3D‐stereophotogrammetry technique to detect differences in facial appearance after a simulated rehabilitation. Materials and Methods: Eleven volunteers without tooth wear participated. A 3D‐stereophotograph was taken in five different situations: resting position, teeth in occlusion, and teeth in occlusion with a 1 mm‐, 3 mm‐ or 5 mm resin block between the first molars. Cephalometric measurements were performed on the 3D‐stereophotographs using the software program Maxilim ® (Medicim NV Mechelen, Belgium). Four anatomical parameters were analyzed: (1) Subnasale–Gnathion, (2) Subnasale–Stomion, (3) Stomion–Gnathion, and (4) Masseter right–Masseter left. A paired Student's T ‐test was applied to detect significant differences ( p  < 0.05). Results: Statistically significant changes in facial appearance of the lower facial height were detected in all measured positions, teeth in occlusion, 1 mm‐, 3 mm‐, and 5 mm block ( p  < 0.05). For the main distance (Subnasale–Gnathion) the mean measured differences were, respectively, 3.2 mm; 5.2 mm; and 6.7 mm. Conclusions: With 3D‐stereophotograph imaging technology, it was possible to detect changes in facial appearance after an artificial increase of vertical dimension of occlusion. This finding implies that reconstruction of loss of tooth substance may cause a visible change in facial appearance of the patient. Clinical Significance: This study reveals a new 3D imaging technique that may be used for a better and more comprehensive treatment planning in patients with severe tooth wear. (J Esthet Restor Dent 28:397–404, 2016)